2015
DOI: 10.5125/jkaoms.2015.41.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor in oral squamous cell carcinoma

Abstract: ObjectivesThe goal of this study was to determine the correlation of clinicopathological factors and the up-regulation of vascular endothelial growth factor (VEGF) expression in oral squamous cell carcinoma.Materials and MethodsImmunohistochemical staining of VEGF and quantitative real-time polymerase chain reaction (RT-PCR) of VEGF mRNA were performed in 20 specimens from 20 patients with oral squamous cell carcinoma and another 20 specimens from 20 patients with carcinoma in situ as a controlled group.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
(30 reference statements)
2
15
1
Order By: Relevance
“…The results support the findings of previous results on the average density of immunohistochemistry (IHC), indicating that in normal oral squamous cells, VEGF expression was detected only in the vascular endothelial cells in the mesenchymal tissues [60,61]. According to these results, to Kim's study on the up-regulation of vascular endothelial growth factor (VEGF) expression in oral squamous cell carcinoma, immunohistochemical staining with VEGF, found a very little expression of VEGF in normal oral squamous cell tissues and a significant positive relationship between VEGF expression and the degree of differentiation or invasiveness of carcinoma [62]. In addition, histopathological findings showed that the VEGF had higher expression levels in less-differentiated invasive oral squamous cell carcinoma, while it was expressed at slightly higher levels in well-differentiated and less-invasive intraepithelial carcinoma tissues or highly differentiated oral squamous cell carcinoma than in normal cells [62].…”
Section: The Role Of Vegf In Metastasismentioning
confidence: 88%
See 1 more Smart Citation
“…The results support the findings of previous results on the average density of immunohistochemistry (IHC), indicating that in normal oral squamous cells, VEGF expression was detected only in the vascular endothelial cells in the mesenchymal tissues [60,61]. According to these results, to Kim's study on the up-regulation of vascular endothelial growth factor (VEGF) expression in oral squamous cell carcinoma, immunohistochemical staining with VEGF, found a very little expression of VEGF in normal oral squamous cell tissues and a significant positive relationship between VEGF expression and the degree of differentiation or invasiveness of carcinoma [62]. In addition, histopathological findings showed that the VEGF had higher expression levels in less-differentiated invasive oral squamous cell carcinoma, while it was expressed at slightly higher levels in well-differentiated and less-invasive intraepithelial carcinoma tissues or highly differentiated oral squamous cell carcinoma than in normal cells [62].…”
Section: The Role Of Vegf In Metastasismentioning
confidence: 88%
“…According to these results, to Kim's study on the up-regulation of vascular endothelial growth factor (VEGF) expression in oral squamous cell carcinoma, immunohistochemical staining with VEGF, found a very little expression of VEGF in normal oral squamous cell tissues and a significant positive relationship between VEGF expression and the degree of differentiation or invasiveness of carcinoma [62]. In addition, histopathological findings showed that the VEGF had higher expression levels in less-differentiated invasive oral squamous cell carcinoma, while it was expressed at slightly higher levels in well-differentiated and less-invasive intraepithelial carcinoma tissues or highly differentiated oral squamous cell carcinoma than in normal cells [62]. In contrast, Shang and Li found that VEGF expression was significantly higher in patients in patients with stage 1 and 2 tumors as compared to when there were a stage 3 and 4 tumors [63].…”
Section: The Role Of Vegf In Metastasismentioning
confidence: 98%
“…Extravasation (diapedesis) of leukocytes into inflamed tissue is aided by VEGF‐A induced permeabilization of blood vessels that were elevated in IL‐1β stimulated hPDLFs. High levels of VEGF have been reported in PD 56,57 and oral cancers 58 where it promotes endothelial cell proliferation and cell migration, along with permeabilization of blood vessels. Additionally, the expression of endothelial adhesions molecules promotes binding of leukocytes onto the subendothelium 59 which is facilitated by ICAM‐1 and VCAM‐1, 60,61 both of which were increased by IL‐1β stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that VEGF affects not only the development of cancer and angiogenesis but also their prognosis. 27 In general, the research results indicate that the average VEGF expression in the group treated with Moringa oleifera leaf extract had a lower value than that of the control group. Such results are consistent with those of the research conducted by Cavell et al 12 which posited that the antiangiogenic activity of isothiocyanate is associated with decreased production of proangiogenic factors, including VEGF.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, VEGF overexpression can be considered a compensation mechanism that allows tumor tissue to increase oxygen uptake through endothelial proliferation. 27 Lalla et al 28 state that the increase in VEGF expression is proportional to the greater density of micro blood vessels in a variety of tumors.…”
Section: Discussionmentioning
confidence: 99%